Fintech advancements in the digital economy: Leveraging social media and personal computing for sustainable entrepreneurship - Brij Gupta; Akshat Gaurav; Varsha Arya; Kwok Tai Chui (Journal of Innovation & Knowledge (JIK), 2024)
Sustainable entrepreneurship refers to the practice of creating and managing a business venture in a manner that is environmentally and socially responsible while still maintaining financial profitability. Social media has become essential for entrepreneurs to build and promote their businesses. It allows them to connect with potential customers, build brand awareness, and reach a wider audience. In recent years, there has been increasing interest in exploring the relationship between sustainable entrepreneurship and social media and how social media can impact sustainable entrepreneurship development. This paper aims to analyze social media's impact on sustainable entrepreneurship development. The study uses data collected from Scopus to identify keywords related to social media, entrepreneurship, and sustainability. Coupling analysis identifies the most frequent keyword groups and clusters and measures their centrality, impact, and color. The results show that social media and entrepreneurship are strongly linked and that social media can positively impact sustainable entrepreneurship development. The study also highlights the importance of ecosystem thinking in promoting sustainable entrepreneurship and the potential of machine learning and sentiment analysis in studying the impact of social media on entrepreneurship. The findings of this study can be useful for policymakers, entrepreneurs, and researchers interested in promoting sustainable entrepreneurship through social media.
Keywords: O30; O31; Q01; L26; 650; Entrepreneurship; Social Media; Machine learning; Research Trends